Youth and the Cuban revolution : youth culture and politics in 1960s Cuba - Luke, Anne (Anne C.) (Lexington studies on Cuba, 2018)
"This study examines youth culture in Cuba in the 1960s. It investigates the lived experience of young Cubans and analyzes how youth identity was constructed within the context of revolutionary policy and discourse"--